Penggunaan Gaya Bahasa Mentor Pada Aplikasi Belajar Online Zenius Education - Pakiding, Ratu Pratiwi; Mayong, Mayong; Fitri, Sakinah (Fakultas Teknik Universitas Negeri Makassar, 2024)
This study aims to describe the use of mentor language style in Zenius Education learning application. The research method used in the study is descriptive qualitative method. The data source is learning videos from Zenius Education application. The form of data in this research is in the form of sentence quotations from the speech of Zenius Education mentors. The collection techniques in this research are observation, documentation, and listening and recording. The data analysis technique carried out by the first researcher converts the data obtained into written form. The data that has been seen in the form of learning videos is then poured into writing. Then the researcher identifies the language style used in the video that has been seen. Finally, the researchers categorised the data through note-taking techniques and drew conclusions. The results show that in the learning videos in the Zenius Education application, the use of official and unofficial language styles is used only to show professionalism and emphasize certain things to form the focus of students in understanding the material while conversational language styles are mostly used in the learning process to create a more active classroom atmosphere.